Literature of Review Influence of Financial Technology, Financial Knowlegde and Financial Behavior to Financial Satisfaction Kredivo Application User Community - Rika Tri Utami; Muhammad Richo Rianto (Draf Solusi Indonesia, 2023)
This research aims to find out how big the influenceis Financial Technology (X1), Financial Knowledge(X2), and Financial Behavior (X3) against FinancialSatisfaction (Y) Kredivo user community. The dataused in this research is primary data. Where, theresearch data was obtained through the results ofquestionnaires distributed online by using the Googleform application. The sample used in this research ispeople who use the Kredivo application. Processingdata on study This will use software smartPLS SEM(Partial Least Square – Structural Equation Modeling)